0336 IMPACT OF BRIEF BEHAVIORAL TREATMENT FOR INSOMNIA (BBT-I) ON SLEEP AND COGNITION IN OLDER ADULTS WITH INSOMNIA: THE REST RANDOMIZED CONTROLLED TRIAL. (28th April 2017) - McCrae, C; Williams, J; Dautovich, N; McNamara, J; Stripling, A; Dzierzewski, J; Berry, R; McCoy, K; Marsiske, M
Abstract: Introduction: Brief (≤4 sessions) behavioral treatment for insomnia (BBT-I) has been shown to improve sleep in older adults with insomnia (OAWI). Despite evidence linking insomnia to complaints of and actual impairments in attention, memory, and executive functioning, behavioral trials rarely include cognitive outcomes. The Research Examining Sleep and Thinking (REST) trial addressed this shortcoming in the literature by examining the effects of BBT-I on sleep and cognitive outcomes in OAWI. Methods: Older adults with chronic insomnia [ N =62, M age=69.45( SD =7.71)] were randomized to 4-weeks of BBT-I ( n =32; education, sleep hygiene, stimulus control, sleep restriction, relaxation) or waitlist control (WLC; n =30). Subjective (sleep diaries) and objective (actigraphy) sleep were assessed daily for 2-weeks, and cognitive tasks were administered during single, 2-hour sessions at baseline, post-treatment, and 3-month follow-up. Sleep variables were averaged over 2-weeks and included: sleep onset latency (SOL), wake after sleep onset (WASO), sleep efficiency (SE), and total sleep time (TST). Cognitive variables included: overall cognitive functioning (WAIS-III-Vocabulary and Digit Symbol); attention, working memory, and processing speed (Trails A & B); language (Controlled Oral Word Association, Boston Naming Test); and memory (California Verbal Learning Test-II, Rey Osterreith Complex Figure, WMS-III-Logical Memory). Results: Using intent-to-treat analyses, subjective SOL, WASO, and SE improved in both groups. Post-treatment improvements were larger for BBT-I versus WLC (all p s<.05; SOL, -23.95 vs -7.11 minutes, η 2 p =.06; WASO, -26.11 vs -5.65 minutes, η 2 p =.12; SE, +10.91 vs +3.27%, η 2 p =.15). At follow-up, gains were well-maintained for BBT-I only. Subjective TST and objective WASO and SE trended toward improvement at post-treatment and follow-up for BBT-I only (TST, +22.80 vs +3.39 minutes, η 2 p =.05, p =.06; WASO, -10.55 vs .85 minutes, η 2 p =.04, p =.09; SE, +1.74 vs -.84, η 2 p =.05, p =.07). Cognitive performance did not improve. Conclusion: BBT-I improved subjective sleep, but did not improve objective sleep or cognitive performance. One possible explanation for our null findings for cognition is that BBT-I may be too short to impact cognition. Another is that our 'single shot' laboratory-based assessments may not be sensitive enough to detect changes in cognition. Future research involving longer treatment and/or daily home-based cognitive assessment may better capture treatment-related cognitive changes in OAWI. Support (If Any): This work was supported by NIH/NIA (R21AG024459, PI: McCrae; T32AG020499, PI: Marsiske).